The Potency of Purple Sweet Potato (Ipomoea batatas) Leaf Extract as Biofungicide for Controlling Fusarium Rot on Chili - Dyah Saputri, Dina; Utami , Annisa Wulan Agus (Future Science, 2020)
Fusarium sp. has been recognized as a pathogenic agent causing fruit rot in chili. The disease significantly decreases the annual chili production rate. One of the plants potentially utilized as biofungicide to control Fusarium fruit rot disease in chili is purple sweet potato (Ipomoea batatas L.). Purple sweet po-tato contains secondary metabolites, mainly the active compounds in the form of flavonoids, which has been previously revealed to perform antifungal activity. This study aimed to examine the potential of purple sweet potato (Ipomoea batatas L.) leaf extract as biofungicide to inhibit the growth of chili rot disease caused by Fusarium sp. within vitro and in vivo assay. This work was conducted by testing the ethanol-extracted purple sweet potato leaves extracts against Fusarium sp. with various concentrations, i.e., 5%, 10%, 20%, and 40% (w/v) for in vitro assay. Then antifungal test against Fusarium sp. was conducted using preventive and curative test for in vivo assay. Observa-tions were performed for 7 days. The result of in vitro assay showed inhibi-tory ability of the leaves extract against the growth of Fusarium sp. to range between 35.2-76.6% with potential concentration 40% (w/v). Based on the results of in vivo assay, the preventive test using 40% concentration of purple sweet potato leaves extract showed significant different against negative con-trol through Duncan test (α = 0.05). Purple sweet potato leaves extract with 40% concentration can reduce the intensity of Fusarium fruit rot disease and potentially utilized as biofungicide.